Comparison of confidence intervals for variance components in an unbalanced one-way random effects model - Arisa Jiratampradab; Thidaporn Supapakorn; Jiraphan Suntornchost (Statistics in Transition new series (SiTns), 2022)
The purpose of this paper is to study and compare the methods for constructing confidence intervals for variance components in an unbalanced one-way random effects model. The methods are based on a classical exact, generalised pivotal quantity, a fiducial inference and a fiducial generalised pivotal quantity. The comparison of criteria involves the empirical coverage probability that maintains at the nominal confidence level of 0.95 and the shortest average length of the confidence interval. The simulation results show that the method based on the generalised pivotal quantity and the fiducial inference perform very well in terms of both the empirical coverage probability and the average length of the confidence interval. The classical exact method performs well in some situations, while the fiducial generalised pivotal quantity performs well in a very unbalanced design. Therefore, the method based on the generalised pivotal quantity is recommended for all situations.
Keywords: 519; variance components; unbalanced one-way random effects model; pivotal quantity; fiducial inference; coverage probability